An Exploratory Study of the Economic and Social potential of Rumbia Village as a Basis for Sustainable Development Planning in the Sub-district - Supriyanto, Supriyanto (Innovative: Journal Of Social Science Research, 2025)
This study explores the economic and social potential of Rumbia Village through a qualitative exploratory approach. Data were collected via observations and in-depth interviews with village officials, MSME actors, and community leaders. Findings indicate that Rumbia Village has strong potential in agriculture, livestock, and micro-enterprises. Socially, values of gotong royong and tight-knit community relations are notable. The community is enthusiastic about empowerment initiatives, but challenges include limited capital, poor infrastructure, and suboptimal support from the village government in human resource development. Inadequate digital infrastructure also limits product marketing reach. Collaboration with NGOs, universities, and the private sector is needed to accelerate local potential development. Training in entrepreneurship and digital skills for youth can foster innovation grounded in local wisdom. A participatory and inclusive empowerment model is vital to achieve economic resilience. Strengthening village institutions and implementing data-based development planning are essential to guide effective interventions. This study emphasizes the importance of collaborative, community-based approaches involving multiple sectors to support sustainable progress. With proper support and coordinated efforts, Rumbia Village has the opportunity to grow into a competitive and self-sufficient rural area. The research offers valuable insights for stakeholders—policymakers, development practitioners, and academics—focused on village development rooted in local strengths and potential. Keywords: Local potential, Rumbia Village, Village Economy, Community Empowerment